Desain UI/UX Aplikasi School Library Berbasis Website Menggunakan Pendekatan HCD - Nirsal; Wahyuni, Choiriyah Nur (Institut Teknologi Garut, 2025)
The rapid development of information technology has encouraged schools to implement digital systems in various aspects, one of which is library management. At SMPN 2 Lamasi, the book borrowing service, which was previously done manually, is now being directed to a website-based system. Through the Human-Centered Design (HCD) approach, this digital library system was developed with consideration of the User Interface (UI) and User Experience (UX) aspects. The HCD approach focuses on user needs and priorities in every stage of the application development process, covering stages from needs analysis to usability evaluation. There are three HCD methods, namely inspiration, ideation, and implementation. The research data collection methods included observation techniques, interviews, and direct testing of users by library staff. The results of the study show that UI/UX design with an HCD approach can improve the usability, efficiency, and user satisfaction of library staff in the book borrowing process at SMP Negeri 2 Lamasi. Thus, this UI/UX design has been proven to be effective in supporting the tasks of library staff without manual recording. The System Usability Scale (SUS) test results showed an average score of 90, which falls into the excellent category with an A grade.